Teologi Misi Holistik: Suatu Diskusi Perspektif Alkitabiah - Missa, Antonius (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2022)
Mission is still misinterpreted with just evangelism and making it a Christian. Holistic mission is a mission that is not limited to witnessing, personal evangelism, but a mission that includes all the teachings of Jesus, such as feeding the hungry, helping the sick, comforting the afflicted and afflicted, suffering, hopeless, unbelieving, and caring. very critical of the government. The purpose of this research is to explain the holistic mission that is biblical. The writing method used is library research with a descriptive analysis approach. The discovery of his writing is in biblical holistic mission theology shows that God uses all things to be used as tools or means for the gospel. Mission is the